Synthesis of Metallo Flavones and Ultrasonic Studies on Chrysin and Morin - Balasubramanian, V.; Muthukumaran, S.; Ravi, A.; Karthikeyan, N.; Rosekumari, I. (Asian Journal of Chemistry, 2016)
Metallo flavones are synthesized and characterized by UV and IR spectral studies. Ultrasonic studies are conducted on certain flavones.